Analisis Framing Pemberitaan Pilgub Jateng pada Harian Suara Merdeka - Nugroho, Adi (Interaksi: Jurnal Ilmu Komunikasi, 2012)
Abstract:  This research has aim to explore how local media cover general election of Central Java Governoor 2008 (Pilgub Jateng 2008). The research concerns on Suara Merdeka Daily Mei-June editions 2008 about news political. The Framing Analysis is used to look how the candidate’s popularity appear on  the newspaper in high frequency. The result of this study is Suara Merdeka Daily Newspaper provide dominant spaces for informing political news of the general election in order to help audience to understand the political issue accured before and during the election. Keywords: frame analysis, Central Java governor election. political news reporting